The African Queen - Forester, C.S.; West, Clare (Oxford : Oxford University Press, 2004)
The African Queen is an unreliable steamboat. No one would take a boat like that down a dangerous river through the jungles of Central Africa during the First World War. But Rose Sayer and Charlie Allnut do just that. They come close to death many times, but no one would expect a missionary's sister and an uneducated mechanic to fall in love.
Nivel 4 (1400 palabras)
BAC
Keywords: Amor, Amor; Aventuras; LIBRO CON PELI; Lengua inglesa -- Lecturas; EXOTISMOS; GUERRA E PAZ